Political conditions of the development of the Polish power grid (Economic and Political Thought, 2022)
The presented text highlights the benefits of making parts of electricity market public comparing to the risks associated with the politicization. The following parts of the article highlight some of the most important problems arising from politicization. These include: investment delays, problems related to the characteristics of the production and connection of energy from renewable sources, and insufficient use of the international integration potential of the power grid. The article also refers to the motivational function of market competition and globalization processes.
Keywords: power grid, electrical grid, politicization, nationalization, public enterprise